Augenblick : Foto\Kunst. - Bösch, Gabriele; Essl, Karlheinz; Frisinghelli, Christine; Iglar, Rainer; Mauracher, Michael; Renner, Lois; Schlegel, Eva (Klosterneuburg (Wien) : Sammlung Essl Kunst der Gegenwart, 2002)
Becher, Bernd & Hilla ; Beecroft, Vanessa ; Belin, Valérie ; Goldin, Nan ; Haider, Ilse ; Helnwein, Gottfried ; Jürgenssen, Birgit ; Kessler, Mathias ; Lafontaine, Marie-Jo ; Moffatt, Tracey ; Neshat, Shirin ; Poirier, Anne & Patrick ; Renner, Lois ; Rheims, Bettina ; Richter, Gerhard ; Ruff, Thomas ; Schilling, Alfons ; Schlegel, Eva ; Scully, Sean ; Sherman, Cindy ; Silvis, John H. ; Struth, Thomas ; Trockel, Rosemarie ; Willmann, Manfred
biog. p. 142-156
Duits & Engels
Augenblick : Foto\Kunst / In the Blink of an Eye : Photo\Art, Sammlung Essl Kunst der Gegenwart, Klosterneuburg (Wien), 15.02.2002 - 30.06.2002, Lois Renner : Itervention, Sammlung Essl Kunst der Gegenwart, Klosterneuburg (Wien), 26.04.2002 - 30.06.2002
boek